THE ESSENCE OF ALIENATION FROM THE PARK BENCH SONG WITH THE TITLE WORKER USING THE APPROACH OF KARL MARX AND FRIEDRICH ENGELS' THOUGHT - Heru Irawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to describe the essence of alienation reflected in the song Pekerja by Bangku Taman, using Karl Marx and Friedrich Engels’ theoretical framework. Alienation in capitalism is understood as the separation of workers from the product of their labor, the production process, their own human essence, and from fellow human beings. The lyric excerpt “Morning, noon, until night / Time passes so quickly / Heat and rain unavoidable / Workers must keep moving” illustrates the exhausting routine of workers, where time flows rapidly without rest, external conditions such as heat and rain cannot be avoided, and yet workers are compelled to continue their labor. This reflects alienation from the production process, which becomes monotonous and inhuman, and alienation from the self, as workers lose opportunities to express creativity and individuality. The findings show that the song Pekerja not only portrays the social reality of the working class but also reinforces the relevance of Marx and Engels’ theory of alienation in contemporary contexts. Music functions as a powerful medium of social critique, voicing the struggles of workers while raising collective awareness of the injustices embedded in capitalist systems.